2015
DOI: 10.3233/bme-151493
|View full text |Cite
|
Sign up to set email alerts
|

Integration of multi-microarray datasets to identify chronic obstructive pulmonary disease-related miRNAs

Abstract: Abstract. Currently, the mechanisms underlying chronic obstructive pulmonary disease (COPD) remain unclear. As potential biomarkers, microRNAs (miRNAs), which modulate the levels of specific genes and proteins, are important for enhancing our understanding of the mechanisms behind COPD. Although there have been a number of miRNA expression profiling analyses strategies used to document miRNA expression changes during physiological and pathological processes or used to identify differentially expressed miRNAs i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…By next-generation sequencing, we found 1,715 differentially expressed miRNAs, and 7 miRNAs (hsa-miR-3177-3p, hsa-miR-19b-3p, hsa-miR-3613-5p, hsa-miR-93-5p, hsa-miR-29a-3p, hsa-miR-142-5p, and hsa-miR-19a-3p) might be novel in COPD. 12 miRNAs (miR-342-3p,32 miR-17-5p,13 miR-16-5p,13 miR-29b-3p,32,33 miR-26b-5p,33 miR-125a-5p,13,34 miR-106b-5p,33 miR-223-3p,35 miR-142-3p,36 miR-30b-5p,36 miR-374a-5p,37 and miR-451a37) had been reported in previous COPD studies. It has been reported that miR-29b38 and miR-106b39 are involved in TGF-β1 signaling.…”
Section: Discussionmentioning
confidence: 99%
“…By next-generation sequencing, we found 1,715 differentially expressed miRNAs, and 7 miRNAs (hsa-miR-3177-3p, hsa-miR-19b-3p, hsa-miR-3613-5p, hsa-miR-93-5p, hsa-miR-29a-3p, hsa-miR-142-5p, and hsa-miR-19a-3p) might be novel in COPD. 12 miRNAs (miR-342-3p,32 miR-17-5p,13 miR-16-5p,13 miR-29b-3p,32,33 miR-26b-5p,33 miR-125a-5p,13,34 miR-106b-5p,33 miR-223-3p,35 miR-142-3p,36 miR-30b-5p,36 miR-374a-5p,37 and miR-451a37) had been reported in previous COPD studies. It has been reported that miR-29b38 and miR-106b39 are involved in TGF-β1 signaling.…”
Section: Discussionmentioning
confidence: 99%
“…The present study compared the obtained list of differentially expressed miRNAs with those previously reported in COPD. The miRNAs that were differentially expressed in this study and previous studies, included hsa-miR-19a-3p, 31 hsa-miR-29b-3p, 32 , 33 hsa-miR-183-5p, 31 hsa-miR-223, 31 , 34 hsa-miR-142-5p, 31 hsa-miR-451, 35 hsa-miR-664, 35 hsa-miR-148a, 35 and hsa-miR-99b. 35 Following integrated analysis of gene transcription and miRNA expression, 42 miRNAs targeting 28 upregulated genes and 69 miRNAs targeting 498 downregulated genes were identified, suggesting that miRNAs may have a regulatory effect on most of the differentially expressed genes in COPD.…”
Section: Discussionmentioning
confidence: 50%